OPTN/SRTR 2020 Annual Data Report: Intestine. (10th March 2022) - Horslen, S. P.; Smith, J. M.; Weaver, T.; Cafarella, M.; Foutz, J.
Abstract: Despite small increases in additions to the intestine transplant wait‐list, total waitlist numbers, overall intestine transplant rates, and overall transplants performed from 2019 to 2020, the trend over the last decade is still toward less intestine transplant activity. Waitlist mortality continues to fall for pediatric populations and is relatively stable for adults. While 1‐year graft survival continues to improve, there has been no noticeable improvement in 3‐ and 5‐year graft survival. Immunosuppression practices continue to favor use of an induction agent followed by tacrolimus‐based regimens. Patient survival at 5 years is currently identical for isolated intestines and liver‐inclusive allograft recipients.